Effectiveness of moist heat therapy on the visibility and palpability of peripheral veins before peripheral venous cannulation among patients undergoing intravenous cannulation (Journal of Pharmaceutical Negative Results, 2022)
Background:A peripheral intravenous cannula is the most frequent invasive medical treatment used to give fluids or medications. Patients who have a fear ofneedles or have had bad experiences with them generally have complications because it activates the sympathetic nervous system and causes peripheral vasoconstriction. Pain alleviation, muscle relaxation, blood vessel dilation, and connective tissue relaxation are the four major effects of heat on bodily tissues.Objectives: This study aims to compare the visibility and palpability of veins in the control and experimental groups of individuals undergoing intravenous cannulation, Evaluate the impact of moist heat treatment on the patients in the experimental group's capacity on visibility and palpability of their veins, Comparing the veins' post-test palpability and visibility in the experimental and control groups of patients having peripheral intravenous cannulation, determine if the sociodemographic information of participants undergoing intravenous cannulation in the control and experimental groups correlates with the visibility and palpability of peripheral veins, find the correlation between the clinical information of patients having intravenous cannulation in the control and experimental groups and the palpability and visibility of peripheral veins.Materials and methods:In the Parul Sevashram hospital in Vadodara, quasi-experimental research was planned to evaluate the impact of moist heat treatment on the visibility and palpability of peripheral veins. A non-probability convenience sampling technique was used for chosen 80 patients undergoing iv cannulation. A socio-demographic and clinical data questionnaire prepared by the investigators and a standardized vein assessment tool (VAT) were used to collect the data from the patients. Using SPSS version 25, inferential and descriptive statistics were utilized foranalysing the data.Results: Given that the pre-test mean and SD in the experimental group were 1.38±0.490 and the post-test mean and SD were 2.55±0.504 at the 0.05 level of significance, the findings showed that moist heat treatment considerably enhanced the vein visibility and palpability. Also, a significant association was found between selected clinical characteristics such as cannula size (p-value 0.000*) and duration of illness (p-value 0.010*) with their VAT scores in the control group.Other characteristics such as diagnosis, type of admission during hospitalization, any previous IV cannulation exposure, number of times of IV cannulation, site of cannulation, and BMI had no association with VAT scores in the control group. In the experimental group, no substantial correlation between clinical variables was discovered. The overall correlation of clinical variables of both groups with the VAT scores indicated a significant association with only one clinical variable, which is the size of the cannula.Conclusion: According to the study, moist heat treatment was successful in increasing the palpability and visibility of peripheral veins before peripheral venous cannulation among subjects undergoing intravenous cannulation.